Perceived vulnerability related to health in cancer post-treated adolescent in Iran: a content analysis - Masumeh Akbarbegloo; Mahnaz Sanaeefar; Mehrdad Karimi; Marzieh Hoseini (BMC Public Health, 2024)
Abstract Background The prevalence of cancer is increasing, which significantly impacts the health and various aspects of the lives of cancer-post-treated adolescents. Adolescents with cancer have many negative consequences, including increased vulnerability. Therefore, this study aimed to explore the perceived vulnerability of cancer-post-treated adolescents using a deep examination of experiences and perceptions of participants. Methods This study was conducted on 18 participants, who were selected based on purposive sampling in 2023 using a qualitative method through a content analysis approach in Iran. A face-to-face and semi-structured individual interview was used to collect data. Inclusion criteria were children aged 11–19 years, with no history of diseases except cancer, at least one year passed since their last treatment and were aware of their disease. Inclusion criteria for other participants were Parents of childhood cancer survivors whose child is under 19 years old. Health care providers that had at least one year of experience working with and caring for pediatric cancer survivors. The research objective, participation principle, and interview recording were explained to the participants before the interview started. The criteria of credibility, dependability, confirmability and transferability were included to support the trustworthiness of data. The data was analyzed using the conventional qualitative content analysis method and MAXQDA10 software was used for data management. Results The participants included 12 cancer-post-treated adolescents, two parents, two nurses, one doctor, and one cancer charity representative. The data analysis identified three categories: “Confusion in early adolescence”, “Psychological turmoil of disease”, and “Physical burden of the disease”. Finally, the latent content was formulated in to a “Perceived vulnerability” overarching theme. Conclusion Identifying the patient’s perceptions and beliefs is one of the current health problems to improve the quality of life and facilitate the optimal transition from adolescence to adulthood and adult care. Health professionals have an opportunity to address factors that increase survivors’ sense of vulnerability to health problems by correcting knowledge gaps.